Identification of hemolysin associated with virulence of streptococcus suis - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
This study was designed to identify hemolysin of Streptococcus suis isolated from diseased and healthy pigs in Indonesia. Hemolysin of S. suis strain D282 has been isolated and purified from culture supernatant by ammonium sulphate precipitation, using filtration steps and Superose-12 column chromatography. All bacterial cultures used in this study were identified as S. suis. Serotyping of the S. suis isolates revealed capsular types 1, 2, 4, and 11 and several cultures were non typeable. The purified hemolysin of S. suis strain D282 had an apparent molecular mass of 31,000-55,000 and exhibited a specific activity of 890 U/ml. Hemolytic activity was reduced after incubation at 37Â°C for 3 hours and after the addition of proteinase K. Most of the different serotype strains appeared to secrete hemolysin. This study indicated that hemolysin could be found in the different serotypes of S, suis. This hemolysin might be used as a protective factor of S. suis.